Action without Reaction: The Case of Beta Equipamentos' Failure in the Colombian and Peruvian Markets - Círico, Maíra (2023)
The purpose of this teaching case is to provide students with an analysis of strategies to enter international markets and stimulate discussion on International Marketing and cultural barriers. The case tells the story of a Brazilian company specialized in the development and manufacture of textile machinery, Beta Equipamentos, which experiences barriers to entry into international markets, specifically in its expansion to Colombia and Peru, countries of the American continent. The company's partners are in a dilemma and need to rethink the entry into the Colombian and Peruvian markets. The use of the case is indicated for undergraduate courses that address themes related to the internationalization of companies, such as modes of entry into international markets, International Marketing and international culture.